Princess Ashley - Peck, Richard, 1934- (New York : Delacorte Press, 1987)
In her new high school, where her mother has taken a job as counselor, Chelsa experiences joys and sorrows as she makes choices about new friends and learns they are not always what they seem.
Booklist.
Notable/Best Books (A.L.A.).
Wilson's Senior High School.
6.0
6.0
7-10.
Keywords: Friendship -- Fiction; High schools -- Fiction; Moving, Household -- Fiction; Schools -- Fiction; Friendship -- Fiction; High schools -- Fiction; Moving, Household -- Fiction; School stories